Help‐seeking among Male Farmers: Connecting Masculinities and Mental Health. Issue 4 (16th April 2014) - Roy, Philippe; Tremblay, Gilles; Robertson, Steven
Abstract In many ways, male farmers can be considered to be a vulnerable group in relation to mental health, experiencing high rates of suicide, psychological distress and low use of health services. This study highlights important connections between rurality, farming and masculinities in the context of men's mental health. In‐depth interviews with 32 male farmers from Quebec, Canada were completed focusing on stress and coping strategies. Findings include informal and formal strategies. Many participants had previous positive experience of formal help and would be willing to use such help again and to recommend it to others in need. Those without such experience are sceptical about services but recognise the courage it requires to seek help. Pride and lack of knowledge about services are the main barriers to help‐seeking, but it can be legitimated in certain contexts, such as divorce or other psychosocial crisis, and by alignment with particular male ideals. Role models at national or local levels can also help farmers prioritise their own and their family's wellbeing over stigmas and rigid, traditional masculine ideals. Furthermore, gender‐based strengths and recommendations for practice are also discussed.